Clinicopathological features, MCPyV status and outcomes of Merkel cell carcinoma in solid-organ transplant recipients: a retrospective, multicentre cohort study - Ferrándiz-Pulido, C; Gómez-Tomás, A; Llombart, B; Mendoza, D; Marcoval, J; Piaserico, S; Baykal, C; Bouwes-Bavinck, J N; Rácz, E; Kanitakis, J; Harwood, C A; Cetkovská, P; et al. (Journal of the European Academy of Dermatology and Venereology, 2022)
BACKGROUND: The proportion of Merkel cell carcinomas (MCCs) in solid-organ transplant recipients (SOTR) harbouring Merkel cell polyomavirus (MCPyV) is unknown, as are factors affecting their outcomes. OBJECTIVE: To describe clinicopathological features of MCC in SOTR, investigate the tumoral MCPyV-status and identify factors associated with tumour outcomes. METHODS: Retrospective, international, cohort-study. MCPyV-status was investigated by immunohistochemistry and polymerase chain reaction. RESULTS: A total of 30 SOTR and 44 consecutive immunocompetent patients with MCC were enrolled. SOTR were younger at diagnosis (69 vs. 78 years, P < 0.001). Thirty-three percent of SOTR MCCs were MCPyV-positive vs. 91% of immunocompetent MCCs (P = 0.001). Solid-organ transplantation was associated with an increased cumulative incidence of progression (SHR: 3.35 [1.57-7.14], P = 0.002), MCC-specific mortality (SHR: 2.55 [1.07-6.06], P = 0.034) and overall mortality (HR: 3.26 [1.54-6.9], P = 0.002). MCPyV-positivity and switching to an mTOR inhibitor (mTORi) after MCC diagnosis were associated with an increased incidence of progression (SHR: 4.3 [1.5-13], P = 0.008 and SHR: 3.6 [1.1-12], P = 0.032 respectively) in SOTR. LIMITATIONS: Retrospective design and heterogeneity of SOTR cohort. CONCLUSIONS: MCPyV appears to play a less prominent role in the aetiopathogenesis of MCC in SOTR. SOTR have a worse prognosis than their immunocompetent counterparts and switching to an mTORi after the diagnosis of MCC does not improve progression.
Keywords: Merkelův nádor; Merkelův polyomavirus; nádory kůže; polyomavirové infekce; lidé; retrospektivní studie; TOR serin-threoninkinasy; Organ Transplantation; Tumor Virus Infections; Carcinoma, Merkel Cell; Retrospective Studies; Skin Neoplasms; Merkel cell polyomavirus; TOR Serine-Threonine Kinases; infekce onkogenními viry; Polyomavirus Infections; transplantace orgánů; Humans